Placental Transfer of a Fully Human IgG2 Monoclonal Antibody in the Cynomolgus Monkey, Rat, and Rabbit: A Comparative Assessment from during Organogenesis to Late Gestation. (April 2014) - Moffat, Graeme J.; Retter, Marc W.; Kwon, Gayle; Loomis, Mark; Hock, M. Benjamin; Hall, Colin; Bussiere, Jeanine; Lewis, Elise M.; Chellman, Gary J.
<x xml:space="preserve">Abstract</x> Understanding species differences in the placental transfer of monoclonal antibodies is important to inform species selection for nonclinical safety assessment, interpret embryo‐fetal changes observed in these studies, and extrapolate their human relevance. Data presented here for a fully human immunoglobulin G2 monoclonal antibody (IgG2X) revealed that, during organogenesis, in both the cynomolgus monkey (gestation day 35 [gd35]) and the rat (gd10) the extent of IgG2X placental transfer (approximately 0.5% maternal plasma concentration, MPC) was similar to the limited published human data for endogenous IgG. At this early gestational stage, IgG2X placental transfer was approximately 6‐fold higher in the rabbit (gd10). By the end of organogenesis, rat embryonic plasma concentrations (gd16) exceeded those in the cynomolgus monkey (gd50) by approximately 3‐fold. These data suggest that relative to the cynomolgus monkey, the rabbit (and to a lesser extent the rat) may overestimate potential harmful effects to the human embryo during this critical period of development. Beyond organogenesis, fetal IgG2X plasma concentrations increased approximately 10‐fold early in the second trimester (gd50–70) in the cynomolgus monkey and remained relatively unchanged thereafter (at approximately 5% MPC). Late gestational assessment was precluded in rabbits due to immunogenicity, but in rats, fetal IgG2X plasma concentrations increased more than 6‐fold from gd16 to gd21 (reaching approximately 15% MPC). In rats, maternal exposure consistent with that achieved by ICH S6(R1) high‐dose selection criteria resulted in embryonic plasma concentrations, reaching pharmacologically relevant levels during organogenesis. Furthermore, dose proportional exposure in both mothers and embryos indicated that this was unlikely to occur at the lower therapeutic dose levels used in humans